Perception of menopause among women of Sarawak, Malaysia - Syed Alwi, Syed Abdul Rahman; Brohi, Bux Imam; Awi, Idi (Springer Nature, 2021)
Background Various factors, including menopausal status, educational and social background, culture, and physical and emotional health, may influence women’s perceptions of menopause. This study documents the elements influencing attitudes towards menopause among women in Sarawak, Malaysia.